2013
DOI: 10.1074/jbc.m113.473819
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Glucocorticoid Receptor (GR) with Estrogen Receptor (ER) α and Activator Protein 1 (AP1) in Dexamethasone-mediated Interference of ERα Activity

Abstract: Background: How glucocorticoids affect ER-positive breast cancer cell proliferation is unclear.Results: GR occupies ERα-binding regions (EBRs) via tethering to AP1 and ERα.Conclusion: Interaction of GR with EBRs via ERα and AP1 inhibits E2-ERα activity.Significance: Breast tumors with ERα and AP1 expression will be responsive to glucocorticoid therapy; the study establishes a foundation for personalized medicine for BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 70 publications
8
113
0
Order By: Relevance
“…Studies show that Dex occupies several ER-binding regions (EBR), and little or less sites are available for E2 binding to its receptor ERa [8]. Further, with increasing the duration of exposure time of Dex to MCF-7 cells, the GR predominantly localized in the nucleus binding to ERa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that Dex occupies several ER-binding regions (EBR), and little or less sites are available for E2 binding to its receptor ERa [8]. Further, with increasing the duration of exposure time of Dex to MCF-7 cells, the GR predominantly localized in the nucleus binding to ERa.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of GC depends on the E2 concentration and the expression of ERa in breast tumor cells. Studies using in vitro model system show that GC inhibits the growth of ERa-positive cells [8]. Estrogens and glucocorticoids have opposing effects on the expression of respective nuclear receptor mRNAs and specific AP-1 factors.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, cistromic profiling of ESR1 and GR in mouse mammary epithelial cell lines revealed significant co-operation of these two NRs, through an assisted loading mechanism, in which binding of one NR facilitates chromatin remodeling thereby enabling access to DNA for the other NR (Miranda et al 2013). Another study profiling ESR1 and GR genomic localization in MCF-7 cells revealed that, although GR co-occupies several ESR1-binding sites in cells treated with both E2 and dexamethasone, GR recruitment to these sites is associated with displacement of ESR1 leading to the repression of estrogen receptor-mediated transcriptional activation of target genes (Karmakar et al 2013). Therefore, although ESR1 co-occupies many target genes with RARA as well as GR, the nature of their interaction is reported to be both co-operative and antagonistic, perhaps reflecting different time, target and cell-specific modes of co-operation between these NRs.…”
Section: Combinatorial Control Of Gene Expression By Nrs In Breast Camentioning
confidence: 99%
“…In contrast to its role in TNBC, the presence of GR in ER+ luminal breast cancers predicts good outcome (Pan et al 2011). Estrogen treatment dampened GR transcriptional activity ), whereas GR directly interfered with ER function, in part via competitive binding to ERα-response elements in DNA (Karmakar et al 2013). In addition to ER and PR (or GR), other SRs (namely, AR) also likely cooperate and interact extensively (including within PELP1 complexes) as part of an emerging paradigm of how cells, including cancer cells, continuously sense and respond to their changing hormonal milieu, and PTMs to SRs and their binding partners likely figure prominently into the mechanisms involved.…”
Section: Figurementioning
confidence: 99%